2020
DOI: 10.1155/2020/8340695
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Functions to Prevent Methylglyoxal-Induced Apoptosis in HK-2 Cells

Abstract: Methylglyoxal (MGO), a reactive carbonyl species, causes cellular damage and is closely related to kidney disease, particularly diabetic nephropathy. Although MGO has been reported to induce autophagy and apoptosis, the relationships between the two pathways are unclear. Here, we evaluated whether autophagy may be the underlying mechanism inhibiting MGO-induced apoptosis. MGO treatment induced concentration- and time-dependent apoptosis in HK-2 cells. Moreover, MGO upregulated the autophagy markers p62 and LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…As observed using these mouse models, renal tubular injury and deterioration of renal insufficiency are more pronounced in ATG-knockout mice after I/R than in control mice, confirming that autophagy exerts a protective effect on mouse renal I/R injury [36,37] . Moreover, the inactivation of autophagy promotes apoptosis, which suggests that increased autophagy inhibits apoptosis and plays a protective role [8,38] …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As observed using these mouse models, renal tubular injury and deterioration of renal insufficiency are more pronounced in ATG-knockout mice after I/R than in control mice, confirming that autophagy exerts a protective effect on mouse renal I/R injury [36,37] . Moreover, the inactivation of autophagy promotes apoptosis, which suggests that increased autophagy inhibits apoptosis and plays a protective role [8,38] …”
Section: Discussionsupporting
confidence: 59%
“…Moderate levels of autophagy are currently thought to play an important role in maintaining the structure and function of tubular epithelial cells. [7][8][9] Recent research has suggested that microRNAs (miRNAs) are closely related to autophagy. [10] miRNAs are single-stranded non-coding RNAs of 19-23 nucleotides that regulate gene expression through the posttranscriptional repression of their target mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…MGO has been reported to decrease cell viability and induce cellular apoptosis in multiple cell types [ 45 , 46 ], including HUVECs [ 47 ]. Our present data clearly demonstrated that MGO treatment significantly reduced HUVEC viability and increased HUVEC apoptosis and that MET protected HUVECs from MGO-induced apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the accumulated MGO further induces oxidative stress, apoptosis and genotoxicity, which plays an important pathophysiological role in the toxic injury of diabetic complications [14–16] . Studies have shown that MGO caused oxidative stress and inflammation in kidney epithelial cell lines (HK‐2 cells), induced apoptosis and autophagy and aggravated the development of diabetic nephropathy [17,18] . In addition, MGO can react with protein, produce advanced glycosylation end products (AGEs).…”
Section: Introductionmentioning
confidence: 99%